The Students’ Perception on the Implementation of Gamification in Learning English at a Private Vocational School - Marningsih, Tri; Sukarno (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigated the students’ perceptions of the benefit of implementing gamification in English learning at a private vocational school. Through a mixed-methods approach, data were collected from surveys and interviews with students who participated in English class utilizing gamified elements. The findings revealed that students perceived gamification as a significant motivator, enhancing engagement, and making the learning process more enjoyable. Additionally, participants reported improvements in language retention and collaboration with peers. However, some challenges, such as varying levels of technological proficiency and potential distractions, were also noted. Overall, this research highlights the positive impact of gamification on students’ attitudes toward learning English suggesting that its integration could be beneficial for educational practices in vocational settings